NGHIÊN CỨU ĐẶC ĐIỂM QUÁ TRÌNH THỦY PHÂN 2-CLOETYLPHENYL SUNFIT TRONG MÔI TRƯỜNG NƯỚC BẰNG PHƯƠNG PHÁP SẮC KÝ - Hoàng, Nguyễn Văn; Khuê, Đỗ Ngọc; Tấn, Đinh Ngọc; Hưng, Đào Duy; Minh, Đỗ Bình (Vietnam Journal of Chemistry, 2012)
Sulphureted chlororganic compounds are high toxic agents for human and animals. Some of them was used as warfare agents. Because of lower toxic level, 2-chloroethylphenyl sulfide was used instead of mustard and similar agents in studying nature of decontamination process on contaminated objects. In this work, the feature of hydrolysis process of 2-chloroethylphenyl sulfide in water is described. It is basic of studying nature of disingtegrating mustard and similar agents by new watered decontamination substances, which are friendly with environment.